Algoritma Perancangan Piranti Lunak Aplikasi Netmap untuk Pemetaan Topologi Jaringan Komputer - Fransiscus Ati Halim; Meilinie Meilinie (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2008)
Two common ways for tackling network problems are troubleshooting or upgrading. For the success ofboth processes, a complete documentation, which encounters a number of essential factors, should be inexistence. Among of these known factors is network topology.When a network is to cover a large geographical area, which is a common case nowadays, the topologymapping is likely to be more difficult. Motivated by this reason, a specific application, called Netmap, wasdesigned to be able to map any given network topology remotely. Through the testing phase on various networktopologies, Netmap showed a success percentage of 88% with an average execution time of 32.05 seconds.Besides, Netmap can provide the user with specific information the about existing devices, such as hostname, IPaddress and MAC address. For further improvement, the future application is expected to be able to deal withextracting more data and compatible on multiplatform.Kata kunci: network topology algorithm